SOME QUESTIONS ON THE DEVELOPMENT OF COMMUNICATION SKILLS OF PRESCHOOLERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the features of the development of communication skills of preschoolers, satisfying one of the most important social needs - the need for communication, which is the basis for the development of his other social needs.